2012
DOI: 10.2337/dc11-1838
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Metabolite Predictors of Glycemia in Middle-Aged Men and Women

Abstract: OBJECTIVEMetabolite predictors of deteriorating glucose tolerance may elucidate the pathogenesis of type 2 diabetes. We investigated associations of circulating metabolites from high-throughput profiling with fasting and postload glycemia cross-sectionally and prospectively on the population level.RESEARCH DESIGN AND METHODSOral glucose tolerance was assessed in two Finnish, population-based studies consisting of 1,873 individuals (mean age 52 years, 58% women) and reexamined after 6.5 years for 618 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
168
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(201 citation statements)
references
References 38 publications
28
168
1
4
Order By: Relevance
“…Alpha-1 acid glycoprotein has been prospectively associated with both fasting and postchallenge glucose [45] and with the risk of developing diabetes [46]. In a recent study among participants from the Estonian biobank, alpha-1 acid glycoprotein was the strongest circulating biomarker predicting all-cause mortality after adjusting for conventional risk factors [8].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-1 acid glycoprotein has been prospectively associated with both fasting and postchallenge glucose [45] and with the risk of developing diabetes [46]. In a recent study among participants from the Estonian biobank, alpha-1 acid glycoprotein was the strongest circulating biomarker predicting all-cause mortality after adjusting for conventional risk factors [8].…”
Section: Discussionmentioning
confidence: 99%
“…A high-throughput NMR metabolomic platform (serum) targeted to multiple pathways with relevance to insulin resistance was employed (http://computationalmedicine.fi/, accessed 10 January 2017) and analyses were carried out in two batches. This NMR metabolite profile has been used for many large-scale epidemiological studies [4,[13][14][15][16][17] and the methodology has been described previously. There are no discernible batch effects [18].…”
Section: Methodsmentioning
confidence: 99%
“…These studies showed that elevated levels of branched-chain and aromatic amino acids and lower levels of glycine are associated with incident type 2 diabetes or deteriorating glucose homeostasis [84,[86][87][88][89][90]. In addition, various lipid species and lipid fractions [85,[87][88][89][90], as well as other small metabolites [87,89,91], showed significant associations with the risk of type 2 diabetes or incident impaired glucose metabolism after adjustment for multiple confounders. Some of the aforementioned studies compared the accuracy of prediction models without and with metabolites (Table 2) and found fairly modest improvements in AROCs for models that included metabolomics in addition to established risk factors for type 2 diabetes [84,88,89,91].…”
Section: Lipids and Small Metabolitesmentioning
confidence: 98%
“…Very recently, data on lipids and small metabolites have become available from prospective studies, and these are summarised in Table 2 [84][85][86][87][88][89][90][91]. These studies showed that elevated levels of branched-chain and aromatic amino acids and lower levels of glycine are associated with incident type 2 diabetes or deteriorating glucose homeostasis [84,[86][87][88][89][90].…”
Section: Lipids and Small Metabolitesmentioning
confidence: 99%